The Effect of the Educational Game Make A Match on Improving Students' Social Interaction - Noor Annisa Anhar; M. Andri Setiawan; Qomario Qomario (Jurnal Evaluasi dan Pembelajaran, 2026)
Social interaction is an important aspect in student development because it plays a role in forming communication skills, cooperation, and positive social relationships in the school environment. However, the reality in the field shows that students' social interactions have not developed optimally. Therefore, innovative and fun learning strategies are needed to improve students' social interactions. This study aims to determine the effect of the Make A Match educational game on improving students' social interactions. A quantitative approach with a pre-experimental design of the One Group Pretest-Posttest Design type was used. The subjects of the study were 32 students of class VII G of SMPN 2 Banjarmasin in the 2025/2026 academic year who were selected using a purposive sampling technique. The research instrument was a social interaction questionnaire that had passed validity and reliability tests. Data analysis was carried out using descriptive statistics, normality tests, homogeneity tests, and hypothesis testing using paired sample t-tests. The results showed an increase in the average social interaction score from 153.53 in the pretest to 167.09 in the posttest. The paired sample t-test results showed a significance value of less than 0.05, indicating a significant difference between social interactions before and after the treatment. Therefore, it can be concluded that the Make A Match educational game significantly improved students' social interactions.